Research of satisfaction of users by educational favour - Olena Myroshnychenko (Cхід, 2013)
In the article the question of satisfaction of users (by potential enterprises - employers) is explored by quality of preparation of young specialists (graduating students of Institute of higher), analysis, which will allow to expose weak sides educations, their improvement and control from the side of guidance of high school.